Genetic resistance to infectious pancreatic necrosis virus in pedigreed atlantic salmon (salmo salar) - Guy, Derrick Richard (The University of Edinburgh, 2011)
Infectious Pancreatic Necrosis (IPN), due to infection with the IPN virus (IPNv), continues to cause heavy mortalities and is endemic across the major Atlantic salmon farming regions of the world. Prevalances of 0.3-0.8 or more at the freshwater stage and 0.05 to 0.3 in the seawater phase of production are typical. Partially effective injectable vaccines are available against seawater IPN but biosecurity measures remain the main methods of control. To explore the feasibility of selecting salmon for resistance to IPN, a selective breeding program was initiated in 1996, including a series of field and experimental trials challenging known full-sib families with IPNv. A total of 404,723 fish faced IPNv challenge (376,541 seawater and 28,182 freshwater) covering 14 years and 17 separate locations across 7 sites. Mortalities and survivors following IPN challenge were counted by full-sib family and analysed as binomial data (alive / dead). Initial heritabilities were obtained from expressions based on the variance and covariance of full-sib family means for the 2001 year-group, indicating heritabilities (h2) of 0.16, range 0.08 to 0.24, and genetic correlations (rg) between replicate families of 0.71 to 0.78. These results were then confirmed by residual maximum likelihood across all seawater challenged data (year-groups 1997-2003), indicating a h2 of 0.43 (s.e.0.02) across all sites, range 0.06 to 0.40 for individual sites, and a range of rg between replicates of 0.70 to 0.87 (s.e. approx 0.05). To accommodate datasets and pedigrees approaching half a million individually identified fish, an implementation of the Reduced Animal model (RAM) was used to obtain these estimates. A similar level of genetic variation for resistance to freshwater IPN (year-groups 2005-2009) was confirmed with a h2 of 0.49, (s.e. 0.03), range 0.31 to 0.59, and rg between replicates ( 0.80 to 0.95, s.e. approx 0.05), using an Individual Animal Model. When all the data were analysed together, assuming seawater and freshwater survival to be the ...